1987
DOI: 10.1111/j.1365-2621.1987.tb06674.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flake Size on Textural and Cooking Properties of Restructured Beef and Pork Steaks

Abstract: Flaked and formed beef and pork steaks were manufactured using eleven different Comitrol cutting heads selected to give a wide range in flake size. Data from texture profile panel, Instron and cooking studies were collected. As flake size increased, visually detected fibrousness, first bite hardness, cohesiveness of the chewed mass, number of chews required for swallowing, amount of connective tissue detected by sensory panel and shear force all increased, while uniformity of the chewed mass decreased. Textura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Chesney et al (1978), McDermott et al (1999) and Berry et al (1999) reported higher tenderness in restructured pork chops, reformed pork shoulder product and cooked beef patties, respectively made with smaller flakes. Berry et al (1987) also found the lower shear force in restructured pork steaks processed from smaller flakes. Suman and Sharma (2003) and Roth et al (1999) reported significant decrease in shear force as the meat particle size decreased.…”
Section: Shear Forcementioning
confidence: 76%
See 1 more Smart Citation
“…Chesney et al (1978), McDermott et al (1999) and Berry et al (1999) reported higher tenderness in restructured pork chops, reformed pork shoulder product and cooked beef patties, respectively made with smaller flakes. Berry et al (1987) also found the lower shear force in restructured pork steaks processed from smaller flakes. Suman and Sharma (2003) and Roth et al (1999) reported significant decrease in shear force as the meat particle size decreased.…”
Section: Shear Forcementioning
confidence: 76%
“…Finer the particle size, the larger is the surface area and greater, the release of muscle proteins. Fine flake size produced a more acceptable appearance, increased tenderness and decreased shear force value (Berry et al 1987). In restructuring, tumbling and massaging are the two techniques routinely used.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of cookout significantly decreased as particle size became smaller (Chesney, Mandigo, & Campbell, 1978). Berry, Smith, and Secrist (1987) indicated that thickness of the flake particle was as important as width of the flake particle in affecting texture. Marriott, Phelps, Costello, and Graham (1986a) showed that particle size had a minimal effect on muscle cut resemblance, cooking loss, shear value, and sensory attributes.…”
Section: Particle Sizementioning
confidence: 97%
“…Marriott et al (1986) showed that particle size had a minimal effect on muscle cut resemblance, cooking loss, shear value and sensory attributes. Berry et al (1987) indicated that thickness of the flake particle was as important as width of the flake particle in affecting texture. Penfield et al (1992) indicated that larger flake size (1.9 cm) and salt improved quality and acceptability of restructured reindeer steaks in comparison with smaller flake size (1.3 cm).…”
Section: Effect Of Meat Particle Size In Restructured Productmentioning
confidence: 99%
“…Berry et al (1987) reported that restructured steak distortion was more extensive in steaks manufactured with large and small meat flakes compared to steaks processed from intermediate size meat flakes. Chen and Trout (1991) observed the diameter change (%) in restructured beef steaks produced with algin/calcium, salt/phosphate, crude myosin, whey protein, wheat gluten, soy protein isolate and surimi and concluded that the diameter of all steaks decreased after cooking and ranged from 12.6 to 17.3%.…”
Section: Shrinkage In Diametermentioning
confidence: 99%